The nutrition situation of free-living elderly in Umlazi township, South Africa - Xolile Mkhize; Carin Napier; Wilna Oldewage-Theron (AOSIS, 2013)
The risk for non-communicable diseases such as hypertension, diabetes, stroke and ischaemic heart disease in the elderly continues to be on the increase. It is shaped and modified by factors such as economic status and experiences across the whole lifespan. Although malnutrition in this population could be due to poor dietary practices, the nutrition transition of communities in South Africa is partially responsible for nutritional problems. Because of the degree of dependency on others for help and care in communities, the elderly are at risk for malnutrition. The elderly of the Umlazi community are overburdened with the social responsibility of grandchildren and trying to bring stability by managing various households. This becomes a double burden and puts more strain on their quality of life, further impacting on their nutritional status.